Self-Concept as a Correlate of Academic Achievement of Special Needs Students in Kwara State - Ifeoma Okafor; Alexander Olushola Iyekolo (Különleges Bánásmód)
Special education has shifted from a position of delivering professional services to students with disabilities to a system that seeks to encompass the broad concept of promoting quality education for students. This study examined the self-concept as correlate of academic achievement of special needs students in Kwara State. The study adopted a descriptive survey research type. Special needs students in the three local government areas in Ilorin, Ilorin South, East and West Local Governments Area constituted the total population for this research.  The researchers designed a questionnaire entitled: self-concept as a correlate of academic achievement of special needs students’ questionnaire” (SCCASNSQ). 200 questionnaire forms were administered. Research questions were answered using mean score, while inferential statistics of mean, standard deviation and Pearson’s Product Moment Correlation (PPMC) were used to test the formulated hypotheses. The finding of the study revealed that academic ability, physical ability, social ability, emotional ability, general self-worth ability and scholastic ability influence self-concept as correlate of academic achievement of special needs students in Kwara State. More so, there was no significant relationship between self-concept and academic achievement of special needs students in Kwara state in Kwara state. There was significant relationship between religion, school type, age and self-concept and academic achievement of special needs students in Kwara State. The findings concluded that while self-concept may not directly influence academic achievement among special needs students in Kwara State, factors such as religion, school type, and age significantly impact both self-concept and academic performance. Based on the findings of the study, it was recommended among others that parents and other stakeholders in the education sector should enhance adolescents’ interpersonal relationship by strengthening their physical, social and emotional self-concepts through relevant social skills training.